How Our Gaze Reacts to Another Person’s Tears? Experimental Insights Into Eye Tracking Technology - Picó, Alfonso; Espert, Raul; Gadea, Marien (Frontiers in Psychology, 2020)
Crying is a ubiquitous human behavior through which an emotion is expressed on the face together with visible tears, and constitutes a slippery riddle for researchers. To provide an answer to the question “How our gaze reacts to another person’s tears?” we made use of eye tracking technology to study a series of visual stimuli. By presenting an illustrative example through an experimental setting specifically designed to study the “tearing effect”, the present work aims to offer methodological insight on how to use eye tracking technology to study nonverbal cues. A sample of 30 healthy young women with normal visual accuity performed a within-subjects task in which they evaluated images of real faces with and without tears while their eye movements were tracked. Tears were found to be a magnet for visual attention in the task of facial attribution, facilitating a greater perception of emotional intensity. Moreover, the inspection pattern changed qualitatively and quantitatively, with our participants becoming fully focused on the tears when they were visible. The mere presence of a single tear running down a cheek was associated with an increased emotional inference and greater perception of sincerity. Using normalized and validated tools (Reading the Eyes in the Mind Test and the SALAMANCA screening test for personality disorders), we measured the influence of certain characteristics of the participants on their performance of the experimental task. On the one hand, a higher level of cognitive empathy helped to classify tearful faces with higher emotional intensity and tearless faces with less emotional intensity. On the other hand, we observed that less sincerity was attributed to the tearful faces as the SALAMANCA test scores rose in clusters A (strange and extravagant) and B (immature and emotionally unstable) of our sample. The present findings highlight the advantages of using eye tracking technology to study non-verbal cues and draw attention to methodological issues that should be taken into account. Further exploration of the relationship between empathy and tear-perception could be a fruitful avenue of future research using eye tracking.